Students' Perception of the "Andy English" Learning Application to Improve Students' Speaking Skill - Siregar, Deva Yanti; Lubis, Yani (Journal of English Language and Education, 2025)
This study investigated the effectiveness of the "Andy English" learning application in enhancing the speaking skills one of Senior High School in Tanjung Balai. Employing a qualitative case study approach, the research explores students’ experiences, challenges, and perceived benefits of using the application through semi-structured interviews and structured questionnaires. The participants, selected via purposive sampling, included Grade X students with varying levels of English-speaking ability. Data were analyzed using thematic analysis for qualitative responses and descriptive statistics for quantitative data. The findings indicate that students perceive the Andy English application as a beneficial tool for improving vocabulary, pronunciation, and overall speaking proficiency. The application’s interactive features, such as conversation practice and grammar exercises, were highlighted as particularly effective in increasing student engagement and confidence in speaking English. The study concludes that integrating mobile learning applications like Andy English can significantly support the development of students’ English-speaking skills and offers recommendations for educators to incorporate such technology into language instruction.